Pareto-improving tax policies under hyperbolic discounting - Kang, Minwook (2021)
This paper investigates the welfare implications of tax policies in the economy with present-biased consumers. We show that consumption taxes, income subsidies, or capital subsidies can improve not only hyperbolically discounted intertemporal utilities, but also exponentially discounted commitment utilities. This finding implies that both consumers and the government can have incentives to adopt tax policies against present-biased decisions. All the results are shown in a three-period model with general utility and production functions. A steady-state analysis indicates that the proposed tax policy is effective in recovering the welfare/capital loss due to consumers’ present bias.